A fala cênica sob o entrelaçamento dos princípios e procedimentos de Konstantin Stanislávski e Declan Donnellan - Vinicius Assuncao Albricker (2014)
The present work explores the stage speech based on the interlacing of the principles and procedures of the Russian master Konstantin Stanislavski and the English director Declan Donnellan. According to the perspective of the Stanislavski system, speech is comprehended as a physical action, considering the investigation of its main qualitative aspects and the effective strategies for its development. On the other hand, in Donnellans context, speech is considered a reaction. Following this, it is assumed, in this work, that the Donnellans concept denominated target appears to be an efficient device for the actor´s formation. In this sense, the reflection proposed herein is concentrated on the actor´s work and aims at contributing to the learning and developing of his/her speech competences. Such competences are linked to three major questions about the stage speech: 1) it is an action that is reactive, objectified, transformative, provocative and replete with expressive nuances; 2) it should not be relegated only to the final moments of creation; 3) it does not depend on the outbursts of inspiration. In this context, two approaches dedicated to the acting practice are articulated: the one of Stanislavski, with the procedures of the physical actions, and the other of Donnellan, with the theoretical-practical fundamentals of the target. As a result, an arrangement of methodological proposals is delineated here which describes didactic examples and suggestions for exercises, all tested and developed in the Fisções Studio and directed to a specific work with the stage speech.